2017
DOI: 10.1016/j.jjcc.2017.07.007
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of eicosapentaenoic acid in patients with coronary heart disease on statins

Abstract: Combination EPA/PTV therapy significantly reduced coronary plaque volume compared to PTV therapy alone. Plaque stabilization was also reinforced by EPA/PTV therapy in particular SAP patients. The addition of EPA is a promising option to reduce residual CHD risk under intensive statin therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
103
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 147 publications
(112 citation statements)
references
References 35 publications
8
103
0
1
Order By: Relevance
“…Nonetheless, patient background (including mean LDL cholesterol and triglyceride concentrations), except for EPA/arachidonic acid ratio, was not statistically different between the two groups ( P = 0.803, Table ). Watanabe et al showed that lipid volume and plaque volume reductions with EPA therapy were independent of decreases in LDL cholesterol and triglyceride concentrations, which is consistent with our results.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Nonetheless, patient background (including mean LDL cholesterol and triglyceride concentrations), except for EPA/arachidonic acid ratio, was not statistically different between the two groups ( P = 0.803, Table ). Watanabe et al showed that lipid volume and plaque volume reductions with EPA therapy were independent of decreases in LDL cholesterol and triglyceride concentrations, which is consistent with our results.…”
Section: Discussionsupporting
confidence: 93%
“…Several intravascular ultrasound or computed tomography studies have shown that EPA therapy attenuates plaque instability . In the present study, multiple regression analyses indicated that previous EPA administration was one of the independent predictors of the characteristics of unstable plaques (Tables ).…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…After 3.2‐year follow‐up, those with phospholipid DHA levels above the median had less atherosclerosis progression as measured with coronary angiography. Two studies in Japanese patients have shown a significant additional benefit of EPA (1800 mg/day) added to statin therapy compared with statin alone on coronary plaque volume, as measured with integrated backscatter intravascular ultrasound 44, 45. In a post‐hoc analysis of 50 diabetics who were randomized to pravastatin or pitavastatin after percutaneous intervention and followed for 8 months, only low DHA levels remained significantly associated with atheroma progression measured by intravascular ultrasound after multivariate regression analysis 46.…”
Section: Discussionmentioning
confidence: 99%